Forms of Interreligious Encounter in Contemporary Nigerian Fiction - Suhr-Sytsma, Nathan (African studies review, 2022)
Africanist scholars continue to debate how best to frame Christian-Muslim encounters. Examining literary fiction that portrays interreligious conflict and dialogue in northern Nigeria, Suhr-Sytsma opens up an exchange between social scientists and Nigerian writers including Chimamanda Ngozi Adichie, Uwem Akpan, Abubakar Adam Ibrahim, and E. E. Sule. Suhr-Sytsma argues that, as social thinkers, Nigerian writers explore interreligious solidarity through forms of doubling and critique forms of sacrifice that authorize scapegoating. Consequently, contemporary Nigerian fiction raises fundamental questions not only about the relation of text to reality but also about the making and crossing of boundaries identified as religious.,